The Psychometrics of Cybersickness in Augmented Reality - Hughes, Claire L.; Fidopiastis, Cali; Stanney, Kay M.; Bailey, Peyton S.; Ruiz, Ernesto (Frontiers in Virtual Reality, 2020)
Augmented reality (AR) is rapidly being adopted by industry leaders and militaries around the globe. With the Defense Health Agency (DHA) pushing AR as a solution to the distributed learning problem, along with AR applications being explored within Primary Care and operational medical settings, it is crucial for these immersive platforms to have a standardized, scientifically based paradigm on which they are designed and used. One area of particular concern is the potential for physiological maladaptation following prolonged AR exposure, which is expected to vary from that associated with virtual reality (VR) exposure. Such maladaptation is potentially driven by limitations that exist with regard to the types and extent of perceptual issues characteristic of AR head-worn displays (e.g., mismatches between visually displayed information and other senses, restricted field of view, mismatched inter-pupillary distance). Associated perceptual limitations can reduce training effectiveness or impose patient and/ or trainee safety concerns. Thus, while AR technology has the potential to advance simulation training, there is a need to approach AR-based research – particularly that which relates to long exposure duration scenarios – from a bottom-up perspective, where its physiological impact is more fully understood. In the hopes of assisting this process, this study presents a comparison of cybersickness between two common forms of AR displays. Specifically, by comparing the Microsoft HoloLens, a head worn display that has seen rapid appropriation by the scientific community, with an AR tablet-based platform within the context of long-duration AR training exposure, it will be possible to determine what differences, if any, exist between the two display platforms in terms of their physiological impact as measured via cybersickness severity and symptom profile. Results from this psychometric assessment will be used to evaluate the physiological impact of AR exposure and develop usage protocols to ensure AR is safe and effective to use for military medical training.